Corrosion prediction for corrosion rate of carbon steel in oil and gas environment: a review - Asmara, Y. P.; Kurniawan, Tedi (Universitas Pendidikan Indonesia, 2018)
Corrosion predictions are essential for corrosion and material engineers. It is used to prepare pre-Front End Engineering Design (pre-FEED). FEED guides to select appropriate materials, planning test schedule, work over management, and estimate future repair for cost analyses. Corrosion predictions also calculate life of pipeline and equipment systems during operational stages. As oil and gas environments are corrosive for carbon steel, it is important to account the corrosion rate of carbon steels in those environmental conditions. There are many existing corrosion predictions software, which are available in oil and gas industries. However, corrosion predictions only can be used for particular ranges of environmental conditions because they use different input parameters. To select the most applicable of corrosion predictions software, engineers have to understand theoretical background and fundamental concept of the software. This paper reviews the applications of existing corrosion prediction software in calculating corrosion rate of carbon steel in oil and gas environmental systems. The concept philosophy of software is discussed. Parameters used and range of conditions are also studied. From the results of studies, there are limitations and beneficial impacts in using corrosion software. Engineers should understand the fundamental theories of the corrosion mechanism. Knowing limitations of the models, the appropriate model can be correctly selected and interpretation of corrosion rate will close to the real data conditions.